APPLICATION OF JIGSAW TYPE COOPERATIVE LEARNING STRATEGY TO INCREASE LEARNING OUTCOMES OF STUDENTS OF CHRISTIAN RELIGION AND CHARACTERISTICS - Irene Juliana Sibarani (Sean Institute, 2022)
Improving Student Learning Outcomes in Christian Religion and Morals Lessons in Class VI through Jigsaw Type Cooperative Learning Strategies at SD Negeri 066667 Medan. The purpose of this study was to improve student learning outcomes in Class VI SD Negeri 066667 Medan in the 2018/2019 academic year. The method used in this research is the Classroom Action Research Method using 2 cycles, the subjects of this research are 18 students of class VI SD Negeri 066667 Medan, the instrument used to obtain data is by using tests, observing the range of scores for the test is 1 - 100.